2004
DOI: 10.1002/ijc.20751
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of peritoneal dissemination of ovarian cancer by tyrosine kinase receptor inhibitor SU6668 (TSU‐68)

Abstract: SU6668 (TSU-68) is a small-molecule synthetic inhibitor of the angiogenic related receptor tyrosine kinases Flk-1/KDR, PDGFR␤, and FGFR1. Using a mouse model of peritoneally disseminated ovarian cancer, we investigated whether SU6668 inhibits peritoneal dissemination and prolongs survival time. BALB/c nude mice were intraperitoneally (i.p.) inoculated with SHIN-3 (VEGF-hypersecretory) or KOC-2S (PDGF-hypersecretory) ovarian serous adenocarcinoma cells with marked peritoneal dissemination ability. From the day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 32 publications
(36 reference statements)
2
24
0
Order By: Relevance
“…We previously reported the inhibitory and survivalprolonging effects of orally-administered TSU-68 on tumor angiogenesis and peritoneal dissemination using a peritoneallydisseminated ovarian cancer model in mice (21). The current study, also using a mouse model, demonstrated the antitumor effects of TSU-68 on subcutaneously implanted endometrial cancer, suggesting the usefulness of molecule-targeting therapy with TSU-68 for endometrial cancer.…”
Section: Discussionsupporting
confidence: 62%
“…We previously reported the inhibitory and survivalprolonging effects of orally-administered TSU-68 on tumor angiogenesis and peritoneal dissemination using a peritoneallydisseminated ovarian cancer model in mice (21). The current study, also using a mouse model, demonstrated the antitumor effects of TSU-68 on subcutaneously implanted endometrial cancer, suggesting the usefulness of molecule-targeting therapy with TSU-68 for endometrial cancer.…”
Section: Discussionsupporting
confidence: 62%
“…The complete clinical data of this trial will be available in the late 2014, and the significance of FGFR2 amplification and other biomarkers on clinical outcomes in this context of the trial will be also investigated. As several FGFR kinase inhibitors are now in clinical trials, including brivanib, dovitinib, BIBF 1120, and SU-6668, it may be useful to test these inhibitors on patients with gastric cancer harboring focal FGFR2 amplifications (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that VEGF secreted by the ROSE199 cells is necessary for the tumor growth. Similarly, SU6668, a kinase inhibitor with broader specificity, was effective in limiting ovarian tumor growth (20,49). Because SU5416 targets host endothelial cells, this treatment may be effective in escaping development of drug resistance common to many chemotherapeutic agents.…”
Section: Cancer Researchmentioning
confidence: 99%